MANAGING AN ORGANIZATION’S CREATIVITY PLANNING BY UTILIZING THE LATEST METHODS AND IMPLEMENTATION MODELS - Mykhaliuk Н.; Binert О.; Miha В. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2025)
Business executives and managers are responsible for identifying unique creative opportunities within their organizations, which influence various social relationships. To effectively plan an organization’s operations and identify optimal management scenarios, it is essential to understand the development processes involved. This includes recognizing the different categories of creative situations, determining the relevant stakeholders, and analyzing the benefits of adopting various approaches, such as individual, collegial, and collective methods, as well as new strategies and models. An effective manager must recognize that both internal and external factors impact the management of an organization's planned creativity. It is vital to know how to manage this creativity and implement it successfully in organizational activities. However, not all companies have the necessary resources and knowledge to manage their planned creativity effectively using new methodologies. Achieving this requires the direct development of creative capabilities, along with the knowledge and evidence gathered from practitioners, which together build the creative potential of the enterprise. Organizations operating in complex socio-economic environments are continually tasked with creating and promoting new creative methods and models to thrive in a competitive market. The success of economic development for businesses largely relies on fostering creative innovations, which are essential for forming competitive advantages. This focus on the management of planned creativity is particularly significant for the ongoing development of Ukrainian society. Ukraine’s recovery from the crisis is tied to enhancing management systems that rely on innovative approaches. The creative development of an organization significantly influences its goals, functions, methods, and structure. This forms an autonomous core within the organization, which plays a crucial role in regulating the overall development processes within the management system, ensuring a smooth integration of science, production, and the market.